GNG12 as A Novel Molecular Marker for the Diagnosis and Treatment of Glioma - Liu, Runze; Liu, Zhendong; Zhao, Yaoye; Cheng, Xingbo; Liu, Binfeng; Wang, Yanbiao; Wang, Jialin; Lian, Xiaoyu; Zhu, Yongjie; Gao, Yanzheng (Frontiers in Oncology, 2022)
Purpose: GNG12 plays a role in a variety of tumors, but its relationship with glioma is still unclear. The purpose of this study was to investigate the relationship between GNG12 and clinical features and prognosis of glioma patients. Patients and methods: The data of glioma and non-tumor brain tissue samples were obtained from the multiple public databases and clinical department. Kaplan-Meier (KM) curves were used to assess the correlation between GNG12 expression and overall survival (OS) of patients. Univariate and multivariate analysis were used to analyze the factors affecting the prognosis of patients with glioma. Gene set enrichment analysis (GSEA) analysis and Tumor Immune Estimation Resource (TIMER) database was utilized to estimate the relationship between GNG12 expression and possible molecular mechanisms and immune cell infiltration. CMap analysis was applied for screening candidate drugs for glioma. RT-qPCR was used to verify the change of expression level of GNG12 in glioma tissues. Results: The expression of GNG12 is closely related to clinical characteristics, including histological grade and histological type (P < 0.001). Univariate and multivariate analysis showed that GNG12 was an independent prognostic factor. GSEA showed that JAK-STAT Signaling Pathway and MAPK Signaling Pathway were highly enriched in GNG12 high expression phenotype. Finally, GNG12 expression is closely related to some immune cells, such as CD8 + T cells, especially in LGG patients. GNG12 may constitute a promising prognostic biomarker in LGG immune cell infiltration. Conclusion: GNG12 is a novel oncogene for glioma, and its overexpression may be closely associated with poor prognosis. GNG12 may affect glioma development through neutrophil and CD8 + T cell related immune processes and other cancer-related signaling pathways. Therefore, GNG12 can be used as a potential biomarker and therapeutic target for gliomas.